Gender Gap in the Writing Practice and Identity Experienced by Male University Students in South Kalimantan - Muhammad Arinal Rahman (Universitas Islam Negeri Antasari Banjarmasin, 2023)
The gender gap between male and female teenage authors causes considerable difficulty in literature. In this work, I employed qualitative research methods to unearth the intricate narratives of personal experiences masked by quantitative research approaches. I used a semi-structured interview format to talk with the participants about their ideas in greater detail. Five university students aged 17 to 19 took part in the study. According to the findings, the absence of gender equality in the writing development of male adolescents is a contributing factor to the gender gap that exists in male adolescents' writing growth. Male and female writing abilities differ significantly, severely impacting young males' educational and professional objectives. By learning more about the writing experiences of college-bound male teenagers, I could gain insights that could be used to improve educational policy and practice. Therefore, it is essential to understand male adolescents' writing identities and provide them with a voice. Additionally, it is essential to learn more about and comprehend the policies and practices that can assist in closing the gender success gap in writing practice.